Fish as biological control agent of golden apple snails-prospects and challenges. - Ali, Jambari; Suryanto, Edi
Fish, especially the benthophagous ones are known to harbor snails. The use of fishes as biological control of molluscs in Israel and Africa is well documented. Field trials on the use of the common carp, Nile tilapia, black carp and hybrid fish to control Pomacea had been carried out in the Phillipines and Vietnam with encouraging results. Pomacea is now considered as a major pest of rice in Asia. Pomacea is more prone as fish prey because of its softer shell and the shell is without nodules and ridges. Two field trials on the use of hybrid catfish to control Pomacea in Malaysia thus far were not so successful. The problems arose from the extreme climatic conditions causing the plastic sheets that partitioned the experimental plots to crumble. Also failure was due to the habit of catfishes escaping by burrowing through the dykes of the experimental plots whenever the water level recede. The experiments somehow shed some insight into the feeding behavior of catfish in the rice field. Some recommendations on the selection of fish for the Pomacea control are given.